Identification and reconstitution of the origin recognition complex from Schizosaccharomyces pombe - Moon, Kyeong-Yeop (The National Academy of Sciences, 1999)
The origin recognition complex (ORC), first identified in Saccharomyces cerevisiae (sc), is a six-subunit protein complex that binds to DNA origins. Here, we report the identification and cloning of cDNAs encoding the six subunits of the ORC of Schizosaccharomyces pombe (sp). Sequence analyses revealed that spOrc1, 2, and 5 subunits are highly conserved compared with their counterparts from S. cerevisiae, Xenopus, Drosophila, and human. In contrast, both spOrc3 and spOrc6 subunits are poorly conserved. As reported by Chuang and Kelly [(1999) Proc. Natl. Acad. Sci. USA 96, 2656–2661], the C-terminal region of spOrc4 is also conserved whereas the N terminus uniquely contains repeats of a sequence that binds strongly to AT-rich DNA regions. Consistent with this, extraction of S. pombe chromatin with 1 M NaCl, or after DNase I treatment, yielded the six-subunit ORC, whereas extraction with 0.3 M resulted in five-subunit ORC lacking spOrc4p. The spORC can be reconstituted in vitro with all six recombinant subunits expressed in the rabbit reticulocyte system. The association of spOrc4p with the other subunits required the removal of DNA from reaction mixture by DNase I. This suggests that a strong interaction between spOrc4p and DNA can prevent the isolation of the six-subunit ORC. The unique DNA-binding properties of the spORC may contribute to our understanding of the sequence-specific recognition required for the initiation of DNA replication in S. pombe.